(untitled) (Homoeopathy for All, 2023)
Early kidney disease is a silent problem, like high blood pressure, and does not have any symptoms. People may have CKD but not know it because they do not feel sick. A person’s glomerular filtration rate (GFR) is a measure of how well the kidneys are filtering wastes from the blood. GFR is estimated from a routine measurement of creatinine in the blood. The result is called the estimated GFR (eGFR). Creatinine is a waste product formed by the normal breakdown of muscle cells. Healthy kidneys take creatinine out of the blood and put it into the urine to leave the body. When the kidneys are not working well, creatinine builds up in the blood. The kidneys maintain the blood creatinine in a normal range. Creatinine has been found to be a fairly reliable indicator of kidney function. Elevated creatinine level signifies impaired kidney function or kidney disease.